Actualization of Potential Life Experience in Normal Aging - Naumova, V; Glozman, J (KnE Life Sciences, 2018)
The paper search mechanisms for maintaining personality well-being at the stage of late ontogenesis, which is important for neuropsychology, gerontology and psychology. The authors analyze the preserved cognitive resource, acquired at the previous age stages, as a resource for life experience mobilization and providing a definite level of intellectual and mental indicators in normal aging. The experience proves that preserved self-regulating abilities in elderly are the main condition of actualizing life experience potential. Specially organized environment in thematic art-groups providing the process of goal-oriented activity and adequate interpersonal interaction is viewed as a determining factor of life experience implementation. The dynamics of viability components reflecting sustainable strategies of self-regulation is investigated and the results of this investigation are presented. Keywords: potential life experience, normal aging, viability, cognitive resource.